2020
DOI: 10.1155/2020/8962635
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Regulatory Roles of lncRNAs in DNA Damage Response in Human Lymphocytes Exposed to UVC Irradiation

Abstract: Long noncoding RNAs (lncRNAs) are a class of noncoding RNAs that modulate gene expression, thereby participating in the regulation of various cellular processes. However, it is not clear about the expression and underlying mechanism of lncRNAs in irradiation-induced DNA damage response. In the present study, we performed integrative analysis of lncRNA-mRNA expression profile in human lymphocytes irradiated with ultraviolet-C (UVC). The results showed that exposure to UVC irradiation dose-dependently increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…These studies provide useful information to understand how cells respond to transcription-blocking DNA damage. An integrated analysis of lncRNA and mRNA expression profiles in UVC-irradiated human lymphocytes was performed by Xu et al ( 37 ). The results revealed that the upregulated lncRNAs were more common than the downregulated lncRNAs with increasing radiation doses.…”
Section: Effect Of Uvr On Ncrnas Expressionmentioning
confidence: 99%
“…These studies provide useful information to understand how cells respond to transcription-blocking DNA damage. An integrated analysis of lncRNA and mRNA expression profiles in UVC-irradiated human lymphocytes was performed by Xu et al ( 37 ). The results revealed that the upregulated lncRNAs were more common than the downregulated lncRNAs with increasing radiation doses.…”
Section: Effect Of Uvr On Ncrnas Expressionmentioning
confidence: 99%